Effect of 6-benzylaminopurine on the production of secondary metabolites of centella asiatica - Badrul Aini, Nurul Iffah (2017)
Centella asiatica L. is commonly known for its medicinal and nutritional values throughout the world. Numerous studies proved the therapeutic effects of this plant including wound healing and anti-inflammatory properties. The medicinal values of this plant were mainly attributed to the presence of several triterpenes, namely asiatic acid, madecassic acid, asiaticoside and madecassoside. The concentration of phytochemicals was found higher in the leaves compared to the roots and petioles. C. asiatica is a subject to exploitation and natural sources of the plant have been vastly depleted. Phytohormone such as 6-benzylaminopurine (BAP) and kinetin are plant hormones that enhance the metabolic activities of plant which results an increase in the production of secondary metabolites, promote growth, formation of leaves and length of shoots. There were not enough study that proves the effect of BAP on C. asiatica. The aim of this study was to evaluate the effect of BAP on the production of triterpene components of C. asiatica. Fresh plants of C. asiatica were divided into two groups; 1) was treated with 2.0 mg/L BAP and 1.0 mg/L kinetin and 2) was under the same controlled growth condition but without both of the phytohormones. They were harvested for 14 days. The triterpenoidal contents were analyzed by using High Performance Liquid Chromatography (HPLC) with DAD detector. Asiatic acid was used as a reference compound and its retention time was recorded at 28. 7 minute while the asiatic acid from the crude extracts was eluted at 39.0 minute using same HPLC conditions. There was significant increase in the production of triterpenoidal components of C. asiatica plant which was treated with BAP.